House Aesthetics and Social Identity: Perigi Village Case Study - Luthfiyah, Luthfiyah Davina Adisti; Tasya , Tasya Fadhilah Amanda; Listen, Listen Prima; Meliansari, Syifa Rahmi; Hidayat, Husnul (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2026)
Palembang’s stilt house is an important cultural heritage that embodies the richness of traditional Indonesian architecture. This study analyses the aesthetic values and social identity expressed in a stilt house in Kampung Perigi, Palembang, and proposes strategies for developing heritage tourism. Using a qualitative descriptive approach, data were collected through field observation, documentation, and a literature review. The findings show that the stilt house owned by Pak Kiagus Amir Hamzah, built in 1930, has distinctive architectural characteristics that blend Dutch influences with local Palembang traditions. Measuring 12 m × 39 m with a floor height of 3.60 m, the building is constructed from ironwood and features ornaments such as lawang kipasan and tiered kijing elements. Heritage tourism strategies recommended for Kampung Perigi include guided historical tours, improved supporting facilities, educational programs, and Musi River boat tours. These initiatives are designed to strengthen heritage conservation while generating community-based economic benefits through local guiding, storytelling, and small-scale tourism services. Beyond description, the study offers a conceptual contribution by showing how hybrid architectural elements can be treated as systematic “identity markers” and converted into clear interpretation themes and tourism products, providing a practical bridge between architectural heritage analysis and community-led tourism planning.